Value-Based Education Model to Enhance Emotional Intelligence, Positive Character, and Fighting Techniques of Junior Tarung Derajat Athletes - Nissa Aldani; Yanuar Kiram; Alnedral Alnedral; Tjung Hauw Sin (JETL (Journal of Education, Teaching and Learning), 2025)
This study addresses the low improvement in training outcomes, particularly in mastering character-intelligence and fighting skills among junior athletes in Tarung Derajat martial arts. The research aims to determine the effectiveness of the BMB3 learning strategy in enhancing these aspects for early-age athletes at Kurata levels III (ages 10–12) and IV (ages 13–14). The study employed an experimental method using a one-group pretest-posttest design. The sample consisted of 30 athletes from the UNP Padang training center, selected through stratified-cluster random sampling. Data collection instruments included a Character-Intelligence Questionnaire and a Tarung Derajat fighting ability test. Descriptive statistics were used to reveal training conditions, while hypothesis testing employed the t-test. The results show: (1) a significant improvement in character-intelligence for 12-year-old athletes (Kurata III) with t = 6.22, p = 0.00; (2) a significant improvement for 14-year-old athletes (Kurata IV) with t = 11.81, p = 0.00; (3) a significant increase in fighting ability for 12-year-olds with t = 6.52, p = 0.00; and (4) a significant improvement in fighting ability for 14-year-olds with t = 7.05, p = 0.00. These findings demonstrate that the BMB3 learning strategy effectively enhances both character-intelligence and fighting skills in junior Tarung Derajat athletes.